Effect of Curcuma Xanthorriza Roxb Extract on Hemozoin Pigment Deposition In The Liver Tissue Of BALB /C Mice Infected With Plasmodium berghei ANKA - Prawesty Utami; Irmawati Dikwan; Ali Wibowo (Future Science, 2020)
Hepatocellular damage is one of the histopathologic features of malaria infection. The presence of large amounts of hemozoin pigment in the liver is associated with hepatocellular damage. Curcuma xanthorriza Roxb / curcumin as an anti-inflammatory and natural antioxidant which has a hepatoprotector function. The purpose of these study was to determine the effect of curcuma rhizome (Curcuma xanthorrhiza Roxb) extract on hemozoin pigment in the liver tissue of BALB/C mice infected with Plasmodium berghei ANKA/ PbA. Method: using 25 groups of BALB/C mice, divided into 5 groups: negative control group; positive control group and 4 treatment groups infected with PbA with extract dose of 150 mg / KgBW, 100 mg / KgBW, and 50 mg / KgBW for four days. On the fifth day the observation of liver tissue to determine deposition of hemozoin pigments by histopathological examination. Results: Statistical analysis showed that descriptively there was a decrease in hemozoin pigment in the liver tissue of mice (150 mg / KgBW extract dose decreased the most hemozoin pigment compared to other doses), but there was no statistically significant difference between the treatment groups with positive controls (p> 0.05). Conclusions: The administration of curcuma extract (Curcuma xanthorriza Roxb) has the potential to reduce the deposition of hemozoin pigment in liver tissue in BALB/C mice infected with Plasmodium berghei ANKA although statistically it is not significant.